Novel functions of non-O1 non-O139 Vibrio cholerae lipopolysaccharide for its haemagglutinating activity - Khan, Summaiya F; Rabbi, Fazle; Ahsan, Nazmul; Yasmin, Mahmuda; Nessa, Jamalun; Ahsan, Chowdhury R (Dhaka University Journal of Biological Sciences, 2011)
Haemagglutinating activity of the surface lipopolysaccharide (LPS) of non-O1 non-O139 Vibrio cholerae was assayed against rabbit and chicken erythrocytes. The serially diluted non-O1 non-O139 V. cholerae LPS showed haemagglutination of rabbit erythrocytes up to a dilution of 1 : 512, which is probably due to the hydrophilic polysaccharide moiety of the LPS. To test whether the LPS was able to bind to glycoproteins and other simple sugars, the LPS was incubated with mucin, glucose and sucrose and was assayed for the residual haemagglutinating activity. It was found that the mucin could inactivate the LPS, which indicated that the LPS of the non-O1 non-O139 V. cholerae strains may bind to glycoprotein and its mechanism of adherence may be similar to that of other bacterial LPS. However, the glucose and sucrose could not inhibit the LPS as has been demonstrated by the positive residual haemagglutinating activity of the LPS.